Enhanced photosensitive properties of a single-crystal formamidinium lead bromide iodine (FAPbBr2I) based photodetector. Issue 4 (20th January 2022) - Gupta, Ramashanker; Gupta, Vinay; Datt, Ram; Arya, Sandeep; Pandey, Animesh; Singh, Anoop; Husale, Sudhir; Srivastava, Ritu; Pathak, Sandeep
Abstract : The growth of FA-based mixed halide perovskite single-crystal via the ITC method has been investigated and characterized to detect its photosensitive properties. The photophysical, responsivity and detectivity also has been investigated. Abstract : In this work, the growth of formamidinium (FA) based mixed halide perovskite single-crystals using the inverse temperature crystallization method is investigated and characterized to detect their photosensitive properties. The structural characterization of the as-grown single crystals was studied using X-ray diffractometry to confirm whether they belong to the {110} family of planes with a high crystallinity. Their optical properties were studied using UV-Vis spectroscopy, which showed a band-gap of 2 eV, and photoluminescence (PL) spectroscopy. The formation of the Ag/FAPbBr2 I/Ag structure was tested under an applied bias voltage of up to ±5 V using different excitation light sources. The results showed a remarkable photosensitive performance with a peak current of 1 μA with corresponding responsivity and detectivity values of 0.8 A W −1 and 1.81 × 10 11 Jones, respectively, under exposure to a visible (376 nm) laser.